The Effect of Location and Price on Consumer Decision in Motorcycle Service Businesses at CV Jaya Agung Mandiri, Ngabang District - Nyemas Anggi Rahayu; Sukardi Sukardi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of location and price on consumer decisions in selecting motorcycle service services at CV Jaya Agung Mandiri, Ngabang District. An associative research design was applied. The population comprised consumers domiciled in Ngabang who had used the workshop’s services, with 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire and tested for validity and reliability. Classical assumption tests (normality, linearity, and multicollinearity) were conducted prior to hypothesis testing. The analysis employed multiple linear regression, correlation and determination coefficients, and simultaneous (F-test) and partial (t-test) significance tests using SPSS 25. The regression model indicates positive coefficients for both predictors (Y = 2.133 + 0.110X₁ + 0.396X₂). The correlation coefficient (R = 0.528) suggests a moderate relationship between the independent variables and consumer decision, while the coefficient of determination (R² = 0.279) shows that location and price explain 27.9% of the variance in consumer decisions, leaving 72.1% attributable to other factors not included in the model. The F-test result (F = 18.745; p < 0.05) indicates that location and price jointly have a statistically significant effect on consumer decisions. The t-test results confirm that each variable has a significant positive effect when assessed separately (location: p = 0.002; price: p < 0.001). These findings imply that, within the observed setting, consumers’ service choices are associated with accessibility-related considerations and perceived price appropriateness, although substantial variance remains unexplained and may involve service quality, trust, or other contextual determinants.